Letramento racial crítico nas séries iniciais do ensino fundamental I a partir de livros de literatura infantil: os primeiros livros são para sempre - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
This research took place in three municipal schools of the public system in Ponta Grossa-Paraná. Its participants were teachers and children from elementar school I. The aim is to understand how the children's literature book can contribute to promote Critical Racial Literacy (CRL) and children's perception of their racial identity, based on the teachers' view. For that, we seek to answer some research questions: How can literature books assist the teacher in building children’s racial identity in elementary school I (initial grades)? What are the perceptions of elementary school children (initial grades) participating in this research regarding to their racial identity? What are the perceptions that the teachers present about the use of the books "Lara’s black dolls", "Betina" and "Each with its own way, each way is one!"? For the analysis, we used the following books of children's literature: “Lara’s black dolls", written by the professor Aparecida de Jesus Ferreira, the book written by the professor Lucimar Rosa Dias, "Each with its own way, each way is one!” and the book “Betina”, written by Professor Nilma Lino Gomes. In order to give theoretical support to this research, authors such as Gomes (2005), Muniz (2010), Melo (2015) Ferreira (2011, 2012), among others, who dedicate their studies to racial issues will be considered. For reflections on literacy(s) we will bring the researchers’ contributions such as: Soares (2000-2004) and Kleiman (2006). About the perspective of teaching from the Critical Racial Literacy: Ladson-Billings (2011) and Ferreira (2014, 2015), which deal with Critical Racial Theory (CRT) in education. About childhood, learning and racial identity, we will make use of the research conducted by Rosa (2014), Jovino (2006), Souza, Dias and Santiago (2017), Dias and Bento (2012) among other authors. The methodology used in this research is qualitative, narrative and case study of the ethnographic type. The instruments for data collection used: questionnaire, classroom observations recorded in the field diary, interviews and autobiographical narratives with the teachers of the observed classes. The (partial) results indicate that it is possible to have classroom dialogues that promote Critical Racial Literacy from the use of children's literature books. The classroom observations during and after storytelling and the teachers' perceptions have shown that children's literature positively contributes to the black child's active participation in the literary environment, in the classroom and in the society, and this contributes to the racial (re) knowledge of the black child, valorization and self-esteem (and this perception is also possible for the white child in relation to the black child). From this perspective, we can conclude from the analyzes made up until the present moment that children's literature can be a facilitating instrument for discussing race in the classroom, since storytelling and literacy practices promote meaningful learning for children, so that they become critical and active beyond the school space.
Keywords: Identidade Racial; Escuta de crianças; Letramento Racial Crítico; Literatura Infantil; Formação de professores; Racial Identity; Childhood; Racial Literacy; Children's literature; Teacher training; CNPQ::LINGUISTICA, LETRAS E ARTES